Sudden Infant Death Syndrome (S.I.D.S). ([Australia] : [publisher not identified], 1968)
Includes articles from the period 1968 to 1992. The articles are on many topics including, statistics on deaths, research and funding, possible causes (sleep position, viruses, dust mites), preventive measures (sleep on back, smoke-free environment, breast feeding), decrease in deaths from 1990s, and red nose day.
Keywords: Sudden infant death syndrome -- Australia -- History; Sudden infant death syndrome -- Australia -- Prevention -- History; Australian